Pendampingan Strategi Digital Marketing Sebagai Upaya Meningkatkan Daya Tarik Wisata Kampung Gerabah Penanggungan - Niken Paramita; Rahayu Puji Suci; Syamsul Bahri; Daiva Permana; Aura Chaerani; Widiya Rahmawati (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This research aims to accompany and develop digital marketing strategies as an effort to increase the tourist attraction of Pananggungan Pottery Village in Malang. Research methods include field observations to analyze conditions, potential and challenges in the village, interviews with various parties including local communities, pottery craftsmen, village administrators, tourists and related stakeholders, as well as FGDs to obtain input and suggestions regarding tourism development strategies. These results are the basis for developing development strategy recommendations, which are then complemented by digital marketing training assistance for the community and tourism actors. By implementing a targeted digital marketing strategy, this research seeks to strengthen the existence of Pananggungan Pottery Village as an attractive and sustainable tourist destination. The methods used in this research involve a series of qualitative approaches, including field observations, interviews with key stakeholders, and FGDs. Field observations provide a comprehensive picture of village conditions, while interviews provide an opportunity to hear the voices of various stakeholders. FGDs were held to gather ideas and further input from stakeholders. Recommendations for tourism development strategies are strengthened by accompanying digital marketing training as a concrete step in implementing the proposed solutions.